2014
DOI: 10.1089/neu.2013.3293
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Self-Administration following Spinal Cord Injury

Abstract: Neuropathic pain develops in up to two-thirds of people following spinal cord injury (SCI). Opioids are among the most effective treatments for this pain and are commonly prescribed. There is concern surrounding the use of these analgesics, however, because use is often associated with the development of addiction. Previous data suggests that this concern may not be relevant in the presence of neuropathic pain. Yet, despite the common prescription of opioids for the treatment of SCI-related pain, there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 82 publications
(124 reference statements)
2
10
0
Order By: Relevance
“…Commensurate with previous studies, 7,8,30 both surgery and morphine administration significantly affected weight gain (Fig. 3).…”
Section: Assessment Of Recoverysupporting
confidence: 87%
See 2 more Smart Citations
“…Commensurate with previous studies, 7,8,30 both surgery and morphine administration significantly affected weight gain (Fig. 3).…”
Section: Assessment Of Recoverysupporting
confidence: 87%
“…There was a significant increase in the lesion size of morphine-treated subjects, and replicating our previous studies, we found that morphine significantly undermined recovery of locomotor function after SCI. [5][6][7][8]30 Despite the loss of neurons, however, repeated morphine administration led to the development of opioid-induced hyperalgesia, with subjects displaying increased reactivity to innocuous mechanical stimulation. As suggested by Garraway and associates, 29 a loss of GABAergic neurons after SCI, and morphine in the current study, may underlie this paradoxical pain hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] To address this, norBNI was administered as an adjuvant to morphine treatment 24 h following SCI, and locomotor recovery was monitored for a 21 day period. Locomotor scores collected before treatment on day 1 did not differ significantly across groups (F [7, Fig.…”
Section: Recovery Of Locomotor Functionmentioning
confidence: 99%
“…[1][2][3][4][5] As opioids are currently among the most effective analgesics for the treatment of pain in the acute phase of SCI, it is essential that we identify the mechanisms underlying these adverse side effects and improve the safety of these medications.…”
mentioning
confidence: 99%